Analysis of proliferative activity and levels of diagnostic cytokeratins expression in epithelial tumors of the ovaries with different malignancy potential - Savchenko, O. A.; Shpon’ka, I. S.; Poslavs’ka, O. V.; Savchenko, P. V. (Морфологія / Morphologia / Morfologìâ, 2017)
Background. Epithelial tumors of the ovaries are quite a diverse group of tumors that have similar macroscopic and variable histological structures with different malignancy potential and make up about half of all ovarian tumors. Depending on the potential of the malignancy, EPIs are divided into benign (25%), borderline (56%) and malignant. Objective. The aim of the study was to compare the expression’s levels of markers of intermediate phyllenes of cytokeratins (CK7, CK20), oncoprotein p53, and the Ki-67 proliferation index, with the observations epithelial tumors to improve the quality of differential-diagnostic immunorphological criteria. Methods. A prospective immunohistochemical study of 70 samples of tumors was carried out among women age from 19 till 76 for compraring histological and immunomorphological characteristics and making retrospective analysis according to cytokeratins (CK7, CK20), p53, Ki-67. Results. The authors distinguished the significant histological characteristics of serous and mucinous epithelial tumors, calculated the proliferation indices for Ki-67 and estimated levels of expression of p53, CK 7 and CK20, depend on the potential of malignancy of tumors. Conclusion. The use of diagnostic cytokeratins CK7 and CK20 is an effective way of determining the type of differentiation of epithelial ovarian tumors (except for the light-cell and endometrioid variants), but only the proliferation index and expression of the p53 tumor marker are important for determining the potential of malignancy.